Wooden architectures: a cartography of Lages-SC - Krahl, Rafael Marcos Zatta; Fiorin, Evandro (Revista Nacional de Gerenciamento de Cidades, 2022)
The primary interest in this article focuses on analyzing the wood architecture in the context of the city of Lages, in the State of Santa Catarina. A work that is produced as an unfolding of other actions and that seeks to build a cartography of wood architectures from the macro-region of the State of Santa Catarina, to a microterritoriality, analyzing the details of a wooden shed in the municipality of Lages-SC. The data used come from bibliographic references and clues about wood architectures derived from a fieldwork, with exploratory character and subject to discovery, surprise and unforeseen circumstances. In this historical process, the architecture in madeira catarinense, in general, accompanied the process of historical, cultural and economic transformation of its context. It begins with indigenous housing, methods brought by Portuguese settlers with the incorporation and adaptations to local resources, changing, later, with the arrival of European immigrants, especially during the nineteenth century, in view of the diversity of cultural traditions and the intensification and mechanization of logging. Thus, it seeks to draw, through data and clues, cartograms that map the wood architecture, in order to characterize its cultural traits, technological roots and vernacular ties. A process that intends, thus, to record the riches of knowledge widespread in most of the construction of popular dwellings in the State of Santa Catarina.